Character Analysis Ability of M. Night Shyamalan Split Translation Film Characters in Indonesian EFL Students - Muthmainnah, Muthmainnah; Marzuki, Abdul Gafur; Santiana, Santiana; Erizar, Erizar; Ulinsa, Ulinsa; Purwaningsi, Utari; B, M. Asri (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The background of this research is to identify or determine the ability to analyze the character analysis of the characters in the film translation Split by M. Night Shymalayan in Semester VI Students of Indonesian Language Education Faculty of Teacher Training and Education in the 2022/2023 academic year. The number of samples in this study is 27 people, class B consisted of 24 girls and 6 boys. Data collection was used, namely test sheets and observation sheets. Then, the data analysis used in this study was the Quantitative Description technique, because the data studied were in the form of technical figures for student learning outcomes by identifying or determining the characters in the Split translation film by M. Night Shymalayan by using a certain formula. The results showed that the students' ability to analyze the characters of M. Night Shymalayan's Split translation film character in sixth-semester students of Indonesian language education experienced differences in every aspect that was assessed. The results of data analysis show that the average score obtained or achieved by class B students in the sixth semester of Indonesian language education obtained an average score of 69.26% with a total percentage of 2.57% in the good category. This means that the split translation film media helps students to identify the character analysis skills of M. Night Shymalayan's split translation film characters.